Healthy lifestyle for women of childbearing age - Hestiyana, Nita; Hidayah, Nurul; Anisa, Fadhiyah Noor; Zulliati (Health Sciences International Journal, 2024)
Background: Maternal nutrition before and during pregnancy is a key determinant of pregnancy outcomes and long-term health for both mother and child. The preconception period is crucial for improving maternal well-being and reducing risks such as preterm birth, low birth weight, and developmental issues. However, many women of childbearing age (WCA) lack adequate nutritional knowledge, increasing the risk of adverse pregnancy outcomes. Case presentation: In collaboration with the Terminal Health Center, a program was implemented to educate WCA on the importance of balanced nutrition and healthy lifestyles to prepare for pregnancy. Activities included a field survey to assess nutritional knowledge, educational outreach through information sessions and leaflets, and monitoring and evaluation of participants' knowledge improvement. Participants actively engaged in discussions, revealing prior gaps in understanding balanced nutrition and its role in pregnancy preparation. Discussion: The preconception period presents an optimal window for nutritional interventions. Addressing micronutrient deficiencies and promoting healthier diets can reduce the risk of complications such as gestational diabetes and preeclampsia. The program demonstrated that educational interventions delivered through community-based healthcare centers can significantly enhance awareness and encourage long-term behavioral changes, ultimately contributing to better maternal and child health outcomes. Conclusion: This intervention successfully increased nutritional literacy among WCA, emphasizing the importance of balanced nutrition in preparing for pregnancy. Cross-sectoral collaborations between healthcare providers and community leaders are essential to sustain these efforts and improve maternal and child health outcomes. Future programs should focus on expanding outreach and continuous evaluation to maintain positive behavioral changes.